Prevalence of female athlete triad among students Universiti Teknologi Mara Cawangan Pahang / Azimah Alias - Alias, Azimah (Faculty of Sport Science and Recreation, 2015)
Female athlete triad is a triad of female problems that it is mainly contributed to the menstrual dysfunction, and energy availability. The purpose of this study is to investigate the prevalence of female athlete triad among students Universiti Teknologi Mara Cawangan Pahang area. The one-way ANOVA analysis is conducted to subjects' population. This study utilized The LEAF questionnaire: for the identification of female athletes at risk for the female athlete triad. Descriptive statistic was used to describe score category. There were 249 subject aged 20.51±1.451 years old subjects which comes from the six different curriculums Based on the results, subjects achieve no risk at 59% good heath ranks and very poor results at risk where 41% female athlete triad difference is 18% percentage. The results show there was no significant mean difference between types of co-curriculum with FAT score. Thus, female athlete triad study is needed for entire subjects to improving health status.